2023
DOI: 10.3389/fnins.2023.1167620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acupuncture in the acute phase of intracerebral hemorrhage on the prognosis and serum BDNF: a randomized controlled trial

Abstract: BackgroundIntracerebral hemorrhage (ICH) is a common cerebrovascular disease, with a high rate of disability. In the literature on Chinese traditional medicine, there is increasing evidence that acupuncture can help hematoma absorption and improve neurological deficits after cerebral hemorrhage. Brain-derived neurotrophic factor (BDNF), one of the most studied neurotrophic factors, is involved in a variety of neurological functions and plays an important role in brain injury recovery. We investigated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Based on the results in Table 6 and Table 3 , it is suggested that motor response was related to disease severity, further confirming the theory above. With the same classifications as our primary outcome, the result suggested that acupuncture could improve the motor response score in the acute phase of TBI, which was consistent with the findings of the RCT on acute-phase ICH subjects by Li et al in [ 22 ], suggesting that acupuncture could improve motor response. Therefore, we could further hypothesize that the effect of consciousness recovery is mainly reflected in motor response recovery based on the above findings.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Based on the results in Table 6 and Table 3 , it is suggested that motor response was related to disease severity, further confirming the theory above. With the same classifications as our primary outcome, the result suggested that acupuncture could improve the motor response score in the acute phase of TBI, which was consistent with the findings of the RCT on acute-phase ICH subjects by Li et al in [ 22 ], suggesting that acupuncture could improve motor response. Therefore, we could further hypothesize that the effect of consciousness recovery is mainly reflected in motor response recovery based on the above findings.…”
Section: Discussionsupporting
confidence: 85%
“…There is also limited evidence to support that the effect of CENA is superior compared to standard acupuncture. The RCT conducted by Li et al also showed significant improvements in the GCS by a median of five points after 12 weeks of intervention in the acupuncture group [ 22 ]. Our baseline data showed that there was a lower percentage of female and higher CAD subjects compared to theirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that acute head acupuncture intervention can improve Clinical Neurological Function Deficit Scale scores in ICH patients (5). Furthermore, Li et al reported that early head acupuncture intervention can improve the level of consciousness and serum brain-derived neurotrophic factor levels in ICH patients (6). Numerous preclinical studies on ICH have demonstrated that acupuncture can improve neurological function in ICH rats by modulating inflammatory factors, cell apoptosis, autophagy, and other mechanisms, thereby alleviating pathological changes in brain tissue (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, acupuncture improves the integrity of the blood-brain barrier by downregulating the expression of caveolin-1 and matrix metalloproteinases (53). Additionally, acupuncture promotes the secretion of neurotrophic factors and angiogenesis around the hematoma following ICH (6,54,55). Based on these mechanisms, acupuncture exerts neuroprotective effects, thereby improving neurological recovery after ICH.…”
Section: Potential Mechanisms Of Acupuncture On Intracerebral Hemorrhagementioning
confidence: 99%